Central Bank communication and the impact of public announcements of new monetary policy data on the reaction of foreign exchange and stock markets: evidence from Poland - Brzeszczyński, Janusz; Gajdka, Jerzy; Ali, M.Kutan (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
We analyze the impact of monetary policy communication of the National Bank of Poland (NBP), i.e. the NBP announcements of interest rates changes and the release of new macroeconomic figures, on the Polish financial market in its two main segments: the foreign exchange market and the stock market, and we provide evidence on how they react to public information from the NBP. In particular, we are interested in the uncertainty (i.e. risk) effects and the wealth (i.e. return) effects of the NBP communication, i.e. whether the NBP announcements had any influence on stock and foreign exchange returns and on the activity of those two markets. Using GARCH methodology, we document the negative effects in the conditional variance of GARCH class models of WIG index volume of trade and WIG returns as well as PLN/USD bid-ask spread and PLN/USD returns, which suggests the existence of the calming effects of the NBP communication with financial markets on their price volatility and on the changes of their activity. The evidence presented in our study indicates that the NBP announcements had stabilizing effects on the stock and foreign exchange markets in Poland
Argumenta Oeconomica, 2017, Nr 2 (39), s. 21-60
Keywords: macroeconomic announcements; interest rates; National Bank of Poland (NBP); foreign exchange markets; stock market; returns volatility; market activity